Dynamics of Tropical Peatlands Characteristics and Carbon Stocks as Affected by Land Use Conversion and Ages of Land Use in Riau Province, Indonesia - Juliano, Gian; Suwardi, Suwardi; Sudadi, Untung (UNIVERSITY OF LAMPUNG, 2024)
The dynamics and patterns of relationships between the characteristics of Indonesian tropical peat involving a function of time (ages of land use) in the context of land conversion have yet to be widely reported. The effects of tropical peatland use change are generally discussed regarding C emissions, with the limited literature identifying dynamic soil characteristics as these changes occur. This study used a survey method. We identified the physical, chemical, and C stock characteristics of peat in forest locations, oil palm plantations with a land use age of 0-5 years,>5-10 years,>10 years, and agricultural land with a land use age of 0-5 years and >5-10 years to find out the dynamics of soil characteristics. Land use changes from peat swamp forests to oil palm plantations and agricultural land, and the longer age of land use results in an increase in BD (especially at the top layer), ash content, pH, Total-N, total-P2O5, total-K2O, but there was a decrease in water content, fiber content, Organic-C, E400/E600, and soil C stocks. The alignment of economic, social, and ecological interests was directed to water and land management by regulating the area’s hydrological system and increasing peat stability.